Strengthening Russia’s International Prestige during the Northern War: Russian Diplomatic Institutions and Instruments - A. V. Topychkanov (Vestnik MGIMO-Universiteta)
During the Northern War (1700-1721), the Russian government had to make great efforts to strengthen the anti-Swedish coalition. Peter the Great developed a broad foreign network of state representatives: employees of the diplomatic corps (envoys, ministers, residents, agents, etc.), trade commissioners, and correspondents. Peter the Great himself, his Cabinet, and the foreign policy department (Posolsky Prikaz, Collegia Inostrannykh Del) controlled these agents of influence. Peter’s diplomats fought for symbolic capital by taking part in official negotiations and unofficial meetings, in diplomatic and court ceremonies, in gift-exchanging, and organizing various festivities. This capital then was converted into the international prestige of the ruler, his title, honor, glory, and position in the hierarchy of European rulers. Considerable attention was paid to promptly inform Western partners about events in Russia’s foreign and domestic policy. Russian information policy emphasized the news that can strengthen Russia’s international prestige: dynastic, diplomatic, and military successes, political reforms, and court celebrations. The article examines the practice of news dissemination through Russian diplomatic missions and foreign diplomatic representatives in Russia. The practice reduced the negative effect of the spread of unofficial information, fake news, and false rumors. The war continued in the pages of print media. To limit the dissemination of information damaging Russia’s prestige, Russian diplomats began to use the same instruments of influence (newspapers, magazines, and pamphlets), which European diplomats used at that time: various methods of pressure and bribery, propaganda, and censorship. The successes of Russian diplomacy have led to the strengthening of Russia’s international prestige and contributed to creating a positive image of the country abroad. The Russian government transferred the gained experience into domestic policy. Peter the Great also demanded fighting against “reprehensible” information about “the person of his majesty, or his troops, as well as his state.”